Association between dietary inflammatory index and risk of endometriosis: A population-based analysis - Liu, Penglin; Maharjan, Rashmi; Wang, Yixiao; Zhang, Yubo; Zhang, Yanqin; Xu, Chunyu; Geng, Yuning; Miao, Jinwei (Frontiers in Nutrition, 2023)
Background and Aims: Chronic inflammation plays a significant role in the etiology of endometriosis, which might be affected by dietary intake. This study aimed to investigate the association between dietary inflammatory index (DII) and the risk of endometriosis. Methods: A cross-sectional analysis using data from the National Health and Nutrition Examination Survey (1999–2006) was conducted on 3,410 American participants, among whom 265 reported a diagnosis of endometriosis. DII scores were calculated based on the dietary questionnaire. The association of DII scores with endometriosis was evaluated by adjusted multivariate logistic regression analyses, which were further investigated in the subgroups. Results: In the fully adjusted models, the odds ratio (OR) for endometriosis participants in the highest and middle tertiles of DII scores were 1.57 (95% confidence interval [CI]: 1.14–2.17) and 1.18 (95% CI: 0.84–1.65), compared to the lowest tertile (Ptrend=0.007). In subgroup analyses, the significant positive association between DII scores and the endometriosis risk was also observed in non-obese women (ORtertile3vs1: 1.69, 95% CI: 1.12–2.55; Ptrend=0.012), women without diabetes (ORtertile3vs1: 1.62, 95% CI: 1.16–2.27; Ptrend=0.005), women with hypertension (ORtertile3vs1: 2.25, 95% CI: 1.31–3.87; Ptrend=0.003), parous women (ORtertile3vs1: 1.55, 95% CI: 1.11–2.17; Ptrend=0.011), and women using oral contraceptives (ORtertile3vs1: 1.63, 95% CI: 1.15–2.30; Ptrend=0.006). Conclusions: This nationally representative study found that increased intake of the pro-inflammatory diet, as a higher DII score, was positively associated with endometriosis risk among American adults. Our results suggested anti-inflammatory dietary interventions may be promising in the prevention of endometriosis. Further prospective studies are necessary to confirm these findings.